Propaganda Politik Hoaks dalam Pemilihan Presiden Tahun 2019 - Rahman Tahir; Heri Kusmanto; Muryanto Amin (Universitas Medan Area, 2020)
The purpose of this research is to find out and analyze the use of hoax propaganda, material or content and patterns of its use in the 2019 Presidential Election. Qualitative methods are used in this research to seek knowledge or understanding of various related relations behind a reality in the new media era, text studies and news documentation and articles about hoax news that can influence the public and can hinder and influence the substance of democracy itself. The results showed that the purpose of hoaks political propaganda in addition to influencing the public was also done to change the negative image into positive or vice versa, in order to increase the electability and popularity of the candidates supported. material or content that is used as propaganda hoaks is material or content that contains SARA, personal, uses a pattern of nicknames, transfers, lure, popular narrative by using news / information content which is negative in nature and even sometimes contains lies using hoax propaganda patterns that are used in the 2019 presidential election. The pattern of the use of hoax propaganda is exhaled in new media by repetitive and continuous ways to change cognitive thinking and arouse the emotions of people who do not understand the deepening of politics.